A Comparative Analysis of SDGs Media Framing in China, Thailand, And Indonesia - Bertha Bintari Wahyujati; Xin Fan; Thanakarn Thanakiatpinyo; Poiluang Konsongsaen (Universitas Negeri Yogyakarta, 2025)
The study looked at national media in China, Thailand, and Indonesia to investigate how they frame the SDGs, following Entman's four framing functions: problem definition, causal interpretation, moral evaluation, and treatment recommendations. Through qualitative content analysis of 52 Indonesian news, 49 Thai news, and 92 Chinese news agency news in the first half of 2025 from the three largest outlets in each of these countries, the study highlights the selective emphasis and different narrative biases conditioned by political systems and media ownership structures. Chinese state media highlighted the SDGs underpinned by national development agendas, such as the infrastructure agenda and climate action, highlighting centralized planning as a success factor while downplaying governance and equality issues. Thai media seems to view things from a technocratic angle, emphasizing innovation and partnerships while leaving aside biodiversity and systemic inequality. Indonesian media focuses more on achievements at the institutional level in poverty and infrastructure, viewing development issues largely as external or technical, while being very reluctant to criticize structural barriers. In all cases, the media narrative tends to legitimize the government's agenda and national image projections rather than nurture them.